Long duration exercise program in individuals with parkinson´s disease: effects on functional capacity - Baptista, André Macari [UNESP]; Beretta, Victor Spiandor [UNESP]; Vitório, Rodrigo [UNESP]; Arroyo, Claudia Teixeira [UNESP]; Lirani-Silva, Ellen [UNESP]; Stella, Florindo [UNESP]; Barbieri, Fabio Augusto [UNESP] (My University, 2014)
The aim of this study was to investigate the effects of long duration exercise program on physical fitness components of functional capacity in individuals with Parkinson disease (PD) and to evaluate ongoing effects of exercise after 8 to 10-week follow-up without exercise. Twenty-four individuals with PD were randomly assigned to two groups: generalized exercise program and stretching exercise program (control group). The generalized exercise program provided training in physical fitness components of functional capacity. The stretching exercise program was characterized by low intensity and volume, mainly with static exercises. Both groups were evaluated before (BI) and after the 4-month (AI) exercise program. In addition, the individuals of generalized exercise program were also evaluated after 8-month exercise program and after 8 to 10- week follow-up without exercise. The generalized exercise program improved flexibility (BI - 38.50±12.42 cm; AI - 44.00±12.74 cm) and agility (BI - 30.59±7.54 s; AI - 28.56±8.20 s) while the stretching exercise program worsened coordination (BI - 23.27±6.58 s; AI - 28.06±7.37 s) and aerobic resistance (BI- 13.64±3.76 min; AI - 17.27±5.15 min) and improved balance (BI - 44.00±7.79 pts; AI - 46.57±6.53 pts). Lower-limb strength and UPDRS-motor scale scores were better at 8 months (14.75±2.92 rep and 26.25±13.97 pts, respectively) compared to baseline (13.13±2.59 rep and 31.63±12.82 pts, respectively) and 4 months (13.50±1.93 rep and 30.38±14.52 pts, respectively) for generalized exercise program. However, the benefits of 8 months of exercise were lost after 8 to 10-week follow-up without exercise (lower-limb strength - 12.43±3.15 rep and UPDRS-motor scale - 32.57±14.05 pts). In conclusion, generalized exercise program improved the functional capacity in individuals with PD, differently of stretching exercise program. In addition, a long duration exercise program promoted benefits for functional capacity and disease progression in individuals with PD. However, benefits were lost after a short period without exercise.
Keywords: Exercise program; Long duration; Functional capacity; Parkinson disease